Treatment of aggression regulation problems with virtual reality: study protocol for a randomized controlled trial - van Wolffelaar, Bas R.; van Horn, Joan E.; Hoogsteder, Larissa M. (Frontiers in Psychology, 2024)
Background: Aggressive conduct among delinquents presents a pervasive issue, bearing substantial implications for not only society at large but also for the victims and the individuals displaying the aggression. Traditional approaches to treating aggression regulation deficiencies generally employ Cognitive Behavioral Therapy (CBT) in conjunction with analog role-playing exercises. A body of research supports the efficacy of various therapeutic models for aggression regulation, including Responsive Aggression Regulation Therapy (Re-ART). Role-playing within a therapeutic context has been shown to contribute significantly to reductions in violent reoffending. However, the practical application of these skills in real-world settings remains challenging due to the inherent risk of aggressive outbreaks. Additionally, the conventional role-playing scenarios, often conducted in a therapy room, lack contextual realism and may induce role confusion between the patient and the therapist. Virtual Reality (VR) technology could offer a viable solution to these limitations by allowing for skill training in both behavioral and cognitive domains within a realistic yet safe and controlled setting. The technology also facilitates real-time awareness of emotional states and tension levels in the patient. This paper describes the study protocol of a randomized controlled trial in which Re-ART offered in a virtual environment (Re-ART VR) is compared to Re-ART offered as treatment as usual. Methods and Analysis: Adult forensic outpatients with aggression regulation problems are randomly assigned to either Re-ART VR or Re-ART. The Controlling Skills, Influence of Thinking and Handling Conflicts modules will be offered to both groups during three to six months. Pre- and post-intervention measurements are performed. The primary outcome measurement is the degree of aggression regulation, while secondary outcome measurements include impulsivity and cognitive biases. Additionally, patient motivation and therapist motivation are expected to act as moderating factors. Discussion: To date, scarcely previous research has been done on the effectiveness of VR in treatment of aggression regulation problems in forensic outpatients. Forensic outpatients who do not benefit sufficiently from mainly CBT-based interventions may benefit more from experiential learning. The unique capabilities of VR in this regard have the potential to enhance the treatment effect.